P Pengaruh Model Pembelajaran VAK Berbasis Whole Brain Teaching Terhadap Kompetensi Pendidikan Agama Hindu Kelas IV - Dayu widya (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The purpose of this research is to determine the effect of Visual Auditory Kinesthetic by Audio Visual Media toward the competence knowledge of science students grade 4 on SDN 2 Ubung. This type of research is quasy experiment with research plan Non-equivalent Control Group Design. The research population is all of Grade 4 students on SDN 2 Ubung districts east Denpasar in academic year 2021/2022. With total population 359 students. The total sample in this research was 86 students,48 students in grade 4A from SDN 2 Ubung whieh became the experiment group and 38 students’ grade 4B from SDN 2 Ubung became control group. Sample selection in this research was using random sampling technique. The students know ledge competence data was collected by using test method which then analyzes t-test. Based on t-test result with freedom degree (dk 84) and on the significance 5% got t.count 3,259 >t.table 2,000so, Who refused and Ha accepted which means there is differences of the group student which were given the study through Viusal Auditory Kinesthetic Learning Model assisted by Audio Visual Media to the 4 grade students on SDN 2 Ubung east Denpasar district on academic year 2021/2022. The result of this research shows that the average value on the experimental group is higher than the average value on the control group (84,13> 76,08) Therefore, the Viusal Auditory Kinesthetic Learning Model assisted by Audio Media affected towards the agama Hindu competency of the 4 grade students on SDN 2 Ubung east Denpasar district in academic year 2021/2022.